Workflow Design and Operational Analysis of a Coal‐Based Multi‐Energy Combined Supply System for Electricity, Heating, Cooling, and Gas - Shiwei Yu; Dedong Li; Zhongyi Zuo; Mingjie Feng (Energy Science & Engineering)
ABSTRACT The combined cooling, heating, and power (CCHP) system, as a typical representative of novel distributed energy systems, demonstrates significant advantages in the cascade utilization of energy and the control of transmission and distribution losses. However, the inherent reliance of traditional CCHP systems on natural gas as fuel structurally conflicts with China's energy endowment, characterized by abundant coal and scarce natural gas, severely limiting their large‐scale application. To adapt to this energy consumption profile and fully leverage the strengths of CCHP systems, this study establishes a coal‐fueled electricity‐gas‐heating‐cooling polygeneration system based on physical and mathematical models within the Aspen Plus 9.0 commercial simulation platform. The reliability of the proposed model is validated through comparisons with data from relevant literature. To identify the optimal operating parameters, the effects of coal‐water slurry concentration and oxygen‐to‐coal ratio on key gasification indicators (e.g., gasifier temperature, syngas composition, syngas calorific value, and cold gas efficiency) and system output loads (e.g., electricity, heating, cooling, and municipal gas) are systematically investigated. Finally, a comprehensive simulation of the entire system is conducted, with energy and exergy analyses performed on major functional units. The results indicate that coal‐water slurry concentration and oxygen‐to‐coal ratio significantly influence gasifier temperature, syngas composition, calorific value, and cold gas efficiency. The system achieves optimal performance at an oxygen‐to‐coal ratio of 1.05 and a coal‐water slurry concentration of 65%. Under design conditions, the system attains a comprehensive energy efficiency of 66.18% and an exergy efficiency of 34.43%. This study provides an innovative solution to address technological bottlenecks in China's energy transition, not only enhancing the efficiency of clean coal utilization but also offering a new technical pathway for coal‐fired power transformation under the “dual carbon” goals (carbon peaking and carbon neutrality).